STUDI FENOMENOLOGI: MEMAKNAI TATA KELOLA PERUSAHAAN PADA BISNIS KELUARGA BERETNIS TIONGHOA DI INDONESIA - R. A. Widyanti Diah Lestari (INVENTORY: JURNAL AKUNTANSI, 2018)
Family business in Indonesia has contributed more than half of Gross Domestic Product (GDP). This makes the presence of family businesses, especially ethnic Chinese, an interesting phenomenon to be studied further. There is still a little theory and research that has been done to explore what happens to ethnic Chinese entrepreneurs because they build successful companies and then transfer to the next generation. So this study aims to gain understanding, interpretmeaning, and state actions taken by parties involved in family business practices, especially those related to the governance, succession and organizational culture of Chinese ethnicity in Indonesia. The results of the literature study show that the source of strength of ethnic Chinese family businessmen lies in their behavior, where in general the social behavior of ethnic Chinese communities still refers to the beliefs of Confusionism teachings and traditional cultural values of their ancestors. The key to success in doing business with Chinese people is better known as the Guanxi, Ganqing, and Xinyong trilogy, which are the characteristics of human relations in the business world that still need to be explored more deeply whether it is appropriate to apply in Indonesia. In running an ethnic Chinese family business, family members are the main character.To avoid agency conflicts and to perpetuate companies that have been pioneered by its predecessor, in some Chinese ethnic family companies in Indonesia a good governance in family business has been implemented through the distribution of share ownership (there is a percentage of ownership), then also a transparent succession process (starting from the deepest family) with the selection process and the transition stage. The progress of a family company can bedemonstrated by increasingly clear rules regarding ownership, management and governance.Keywords: family corporate governance, trilogy (Guanxi, Ganqing, and Xinyong)